Penguatan Peran Anggota PKK Kenagarian Pungguang Kasiak dalam Pengelolaan Sampah Organik dan Anorganik Berbasis 3R - Awalina, Rahmi; Putra, Haznam; Lestari, Resti Ayu (Warta Pengabdian Andalas, 2024)
This community service activity aims to increase the awareness and skills of Empowerment Family Welfare (PKK) members in managing inorganic waste, encouraging household economic independence through a waste bank-based savings system. The program was implemented at the Pungguang Kasiak Village Office, Lubuk Alung District, Padang Pariaman Regency. A participatory and educational approach was used in this activity, consisting of socialization regarding the importance of waste management, technical training in waste sorting, weighing and assessing waste with economic value, and forming structured working groups under the coordination of the PKK. The activity also includes monitoring and evaluating the effectiveness and impact of improving the family economy. The activity results show that this approach can empower PKK members as agents of environmental change and drive forces for the family economy through sustainable household waste management.